A behavioural model of heuristics and biases in frontline policy implementation. (1st January 2021) - Moseley, Alice; Thomann, Eva
Abstract : This article theorises how behavioural public administration can help improve our understanding of frontline policy implementation. The human factors that characterise policy implementation remain undertheorised: individual variation in policy implementation is dismissed as mere "noise" that hinders predictability in policy implementation. This article aims to fill this gap. We provide a model for street level decision-making which outlines the role of heuristics and biases in frontline workers' allocation of resources and sanctions. Based on an analysis of the behavioural and street-level bureaucracy literature, we present 11 testable propositions that point to predictable patterns in the ways that bounded rationality influences policy implementation and outcomes. Heuristics can help hard-pressed frontline public service workers to make decisions but may also produce social inequity or inefficient or ineffective service. Therefore, we need to improve understanding of biases that are common among frontline workers in order to inform the development of appropriate mitigation strategies, such as de-biasing or even 're-biasing' (nudging).